Organics and fertility levels influences barley yield and soil properties in semi-arid region of Rajasthan - Kumawat, Sita; Sharma, S. R.; Rundala, S. R.; Dogra, Prerna (Annals of Agricultural Research, 2016)
A field experiment was conducted for two consecutive rabi (winter) seasons of 2011-12 and 2012-13 at the Agronomy Farm of S.K.N. College of Agriculture, Jobner, Rajasthan to evaluate the effect of organics and fertilizer levels on barley yield and soil bio-chemical properties. The application of vermicompost @ 5 t ha-1 + biofertilizers significantly increased the grain yield of barley by 29.23%, mean over two years of study. Addition of FYM and vermicompost alone or in combination with biofertilizers showed significant improvement in soil nutrient availability, dehydrogenase and alkaline phosphatase activities and microbial biomass carbon, nitrogen and phosphorus after harvesting of barley over control. Among the organics, the application of vermicompost @ 5 t ha-1 + biofertilizers recorded improvement in all the soil properties. Fertilizing the crop with 75% RDF gave significantly highest grain yield of barley over unfertilized plots. Application of increasing levels of chemical fertilizers also improved the soil bio-chemical properties over control.